Risk Factors of Mid-upper Arm Circumference (MUAC) Based Child Malnutrition in the Flood-affected Areas of Pakistan: A Cross-sectional Study: Child malnutrition in flood-hit areas. Issue 4 (4th July 2021) - Haq, Ijaz ul; Mehmood, Zafar; Khan, Nadar; Khan, Muhammad Nadeem; Israr, Muhammad; Ali Khan, Ejaz; Nisar, Muhammad; Ahmad, Muhammad Ijaz; Ali, Majid
ABSTRACT: Low- and middle-income countries are usually at high risk of malnutrition. Not only that but the prevalence of malnutrition is much higher. It is important to evaluate the determinants of malnutrition in flood-affected areas of Pakistan. The present study examined the prevalence and risk factors of MUAC-based child malnutrition in flood-hit regions of Khyber Pakhtunkhwa, Pakistan. Multi-stage sampling was employed to select 656 households. Finally, 298 children of 6–59 months were selected. MUAC, an independent anthropometric parameter, was used to investigate the nutritional status of children. An automated logistic regression model was used to identify the risk factors of MUAC-based malnutrition. The prevalence of MUAC-based malnutrition was found 46%, including 40.5% females and 52.1% males. More than 90% of people had improved water quality and soap hand washing facility. Almost 17% of respondents had no toilet facility. Through automated logistic model, child age, maternal age, family size, income level, mother education, water quality, toilet facility were the significant determinants ( P < .05) of MUAC-based undernutrition in flood affecting the area. The findings suggest that MUAC-based malnutrition can be minimized in flood-hit areas by targeting the listed risk factors. Community-based awareness programs regarding guidance on nutrition might be a key to reducing malnutrition in the target areas.